“El amor al arte necesita fondos para que funcione”: Dinámica Artístico-Económica entre los Productores de Eventos en la Escena Musical Electrónica de Posadas, Misiones, Argentina - Fank Ríos, Ricardo Aníbal (Notas de Antropología de las Américas, 2023)
Based on an empirical investigation of the “electronic music scene” of the capitalcity of a peripheral province in Argentina, I try to contribute to an anthropologicaldefinition of the “event producer” as an economic subject that works and trades,and also develops artistic criteria of “curatoship” that differentiate him from DJs,producers and bolicheros (owners of dance venues). I affirm that with an “event”he simultaneously produces a commodity and a piece of art.